Entrance and lettering, Empress Court - Ghosh, Ayan (Jio Institute, 2023)
Entrance and lettering, Empress Court. Built in 1933-39, Empress Court was designed by architects Contractor and Kanga with additional designs by Gajanan Babu Mhatre. Most of the residential buildings along Maharshi Karve Marg were designed by Indian developers and architects, rather than British architects.